PEMBAGIAN HARTA PENINGGALAN KEPADA AHLI WARIS MENURUT KITAB UNDANG-UNDANG HUKUM PERDATA - Dio Prastika Kris Juniawan; Suparsetyani, Endang (Faculty of Law, Universitas Trisakti, 2023)
Whoever has the right to represent themselves as an heir and the portion they receive is still a concern when a person passes away and their assets are passed to their heirs. The problem that needs to be solved in this study is how to distribute the heirs' inheritance to their heirs according to the Civil Code and whether or not the decisions made in Surabaya District Court Judge Number 973/Pdt.G/2021/PN Sby regarding who would inherit from the heirs of the heirs were appropriate or not. The study's findings, analysis, and recommendation are the distribution of the heirs' inheritance to those of their heirs according to the Civil Code, namely Maity Kaseger and Henriette Beatrix Kaseger, Egenio Mario Nicolas, Stella Thesia Nordie Kaseger, F. Mario Bartolomeus Kaseger, P.J Argo Kaseger, Raphael Mario Angelo. The Surabaya District Court Judge decision number 973/Pdt.G/2021/PN Sby decided that who became the heir of the heir was not in accordance with the Civil Code where the sons-in-law, namely Bing Tjoei and Sri Wurjanti Hartono were included in the inheritance of the heir's inheritance while according to the Civil Code the sons-in-law had no right to inherit because they were not blood related to the heir.